2017
DOI: 10.18844/gjpr.v7i1.2431
|View full text |Cite
|
Sign up to set email alerts
|

The importance of listening in communication

Abstract: Listening skills have been a great concern for both researchers and teachers trying to promote communicative competence. The purpose of this study is to find out to what extend listening is important in gaining communicative competence. 100 university level preparatory class students were chosen as subjects of the study. Students took formal listening and speaking classes for one term and at the end of the term they took a written exam for listening class and an oral exam for speaking class. The data obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…88% of the respondents are self-motivated because they think listening skill is important. Listening skill is said to be an important agent in oral production by establishing a foundation for speaking in the language (Yavuz & Celik, 2017). Therefore, through this realisation, the pupils would be able to put in some effort during the listening lessons.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…88% of the respondents are self-motivated because they think listening skill is important. Listening skill is said to be an important agent in oral production by establishing a foundation for speaking in the language (Yavuz & Celik, 2017). Therefore, through this realisation, the pupils would be able to put in some effort during the listening lessons.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…A few researchers have given more importance to other skills than listening. However, Yavuz & Celik (2017), it is not simple to exclude listening from language learning due to its vitality in communication. In a study carried out by Yildrim & Yildrim (2016) listening takes up 40 -50 % of the time in communicating and the other skills which are speaking, reading, and writing comprise another 50% which is eventually less than the listening time taken.…”
Section: Listening Skill Strategiesmentioning
confidence: 99%
“…After reviewing related studies on importance of listening skills in higher education, the researcher found its significant contribution in improvement of vocabulary ( (Yavuz & Celik, 2017), classroom dynamics which inevitably leads to successful adjustment in learning environment and also helps to cope with stressful situations. But, inadequacy of systematic studies relating to its relation to academic performance as well as underlying factors associated with variation in listening skills let the researcher reflect upon and identify the need to study the same on students of disadvantaged social groups at higher education in West Bengal.…”
Section: Problem Statementmentioning
confidence: 99%